Asas-Asas Kepemimpinan Hindu Dalam Lontar Niti Raja Sasana - I Wayan Sukabawa (Jurnal Penelitian Agama Hindu, 2019)
Lontar is a document that is considered to be relics that have special values, namely spiritual and cultural values, and economic values. Lontar which has socio-cultural values ​​is the work of a person or group of people who preserve local cultures. Lontar has values ​​that are in contact with the life of the wider community or contain norms of community life, both individually and in groups (organizations), which must be preserved which will later be able to be passed on by the younger generation. In ancient times lontar-lontar received special attention, because it contains values ​​that are considered sacred. It should not be haphazardly people who open and read it, so that the contents of the lontar are rarely known, sometimes very confidential (ajawera). The language used in lontar is a mixed language, namely Old Balinese, Old Javanese and Sanskrit. In the current era of globalization, young people are very rarely willing to read lontar. That was caused by: (1) seeing the shape of the younger generation had underestimated; (2) the language used in ejection is a language that is difficult to understand; (3) the writing form is rarely found except in certain places such as museums, libraries and others.